Hubungan industri dan sumber manusia : isu dan perspektif - Dzurizah Ibrahim; Parasuraman, Balakrishnan; Rosazman Hussin; Universiti Malaysia Sabah (Kota Kinabalu, Sabah : Universiti Malaysia Sabah, 2009)
Issues on industrial relations, human resources development, and personnel management in Malaysia; collection of articles.
Includes bibliographical references and index.
In Malay.
Keywords: Industrial relations -- Malaysia; Personnel management -- Malaysia